Strategi Tutor dalam Meningkatkan Partisipasi Warga Belajar dalam Proses Pembelajaran di PKBM Laskar Pelangi - Zahra Darmayana; Mahfuzi Irwan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The study was motivated by the low participation of learners, as indicated by inconsistent attendance and lack of active involvement during the learning process. The focus of this study includes tutor strategies in planning, implementing, and evaluating learning activities. This study aims to analyze tutor strategies in improving the participation of Package C learners in the learning process at PKBM Laskar Pelangi. This study used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The results showed that tutor strategies were implemented through adjusting learning to learners’ conditions, using interactive methods and learning media, providing motivation, applying discussions and question-and-answer methods, using personal approaches, giving learning stimuli, and conducting evaluations through assignments, exercises, interactive quizzes, and feedback. These strategies helped improve learners’ comfort, attention, and involvement during the learning process. Thus, tutor strategies play an important role in increasing the participation of Package C learners at PKBM Laskar Pelangi.